Implementasi Algoritma Regresi Linear Dalam Sistem Prediksi Pendaftar Mahasiswa Baru Sekolah Tinggi Teknologi Indonesia Tanjungpinang - Nanny Raras Setyoningrum; Putri Jingga Rahimma (Prosiding, 2022)
In the last four years, Sekolah Tinggi Teknologi Indonesia Tanjungpinang has experienced ups and downs in the number of new students. In the 2017/2018 academic year the number of new students was 180 with 77 students taking the Information Systems study program and 103 students choosing the Informatics Engineering study program. In the following year the number of students decreased by 16% then rose again in the 2019/2020 academic year by 23% with 185 new students and in the 2020/2021 academic year where this year the whole country was hit by the Covid-19 pandemic, it decreased again by 8, 6% with 169 students. The use of linear regression algorithms in predicting the number of new students in the form of a web-based application can facilitate the marketing department in making future strategies to increase the number of new students in the following year. The method in this research consists of several stages, namely literature study, data collection, system requirements analysis, system design using simple linear regression algorithm, python django programming language and using MySQL database, then implementation and analysis of results and testing. The results of this study can help predict the number of new students for the future, where the results obtained are estimates based on data for a certain period of time. The accuracy test with manual calculation is 0.000277008 while the accuracy test with the system is 0.00027700831024, this shows that manual calculations and system calculations can be said to be appropriate